Phase 3 Trials of Thermosensitive Ciprofloxacin Gel for Middle Ear Effusion in Children with Tubes. (22nd July 2016) - Park, Albert H.; White, David R.; Moss, Jonathan R.; Bear, Moraye; LeBel, Carl
Abstract : Objective: To investigate the efficacy, safety, and microbiology of a thermosensitive otic suspension of ciprofloxacin (OTO‐201) in children with bilateral middle ear effusion undergoing tympanostomy tube placement. Study Design: Two randomized, double‐blind, sham‐controlled phase 3 trials. Patients were randomized to intratympanic OTO‐201 or sham. Setting: Children with bilateral middle ear effusion undergoing tympanostomy tube placement. Subjects/Methods: Studies evaluated 532 patients (6 months to 17 years old) in a combined analysis of efficacy (treatment failure: presence of otorrhea, otic or systemic antibiotic use, lost to follow‐up, missed visits), safety (audiometry, otoscopy, tympanometry), and microbiology. Results: There was a lower cumulative proportion of treatment failures in patients receiving OTO‐201 vs tympanostomy tubes alone (1) on days 4, 8, 15, and 29; (2) on day 15, primary end point (23.0% vs 45.1%; age‐adjusted odds ratio, 0.341; P <. 001; reduction in relative risk, 49%); and (3) on day 15, blinded‐assessor otorrhea treatment failure (7.0% vs 19.4%; age‐adjusted odds ratio, 0.303; P <. 001; reduction in relative risk, 64%). Per‐protocol and subgroup analyses (baseline demographics, pathogen type, culture status, effusion type, microbiologic response) supported these findings. There were no drug‐related serious adverse events; the most frequent treatment‐emergent adverse events in both groups were pyrexia, postoperative pain, nasopharyngitis, cough, and upper respiratory tract infection. OTO‐201 administration had no evidence of increased tube occlusion and no negative effect on audiometry, tympanometry, or otoscopy. Conclusions: Combined analysis of 2 phase 3 trials demonstrated a lower cumulative proportion of treatment failures through day 15 compared with TT alone when OTO‐201 was administered intratympanically for otitis media with bilateral middle ear effusion at time of tympanostomy tube placement.